The Influence Of Capital Intensity, Managerial Ownership, Leverage And Financial Distress On Accounting Conservatism In Manufacturing Companies Listed On The Bei In 2019-2023 - Apriani, Lusy; Hadli, Hadli; Wijaya, Angka (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Accounting conservatism as a principle of prudence in financial reporting where the company is not in a hurry to recognize and measure assets and profits and immediately recognizes losses and debts that have the possibility of occurring. The factors that influence accounting conservatism are: capital intensity, managerial ownership, leverage and financial distress. The purpose of this study was to determine the effect of capital intensity, managerial ownership, leverage and financial distress on accounting conservatism in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Type of research used Quantitative research. The data used is secondary data. The population is 215 companies and the sampling technique uses the Purposive Sampling method. A sample of 41 companies x 5 = 205 financial report data was obtained. The analysis used panel data regression analysis method using Eview 13 software. The results of partial testing show that capital intensity has a significant effect on accounting conservatism, managerial ownership does not have a significant effect on accounting conservatism, leverage does not have a significant effect on accounting conservatism and financial distress does not have a significant effect on accounting conservatism. The results of simultaneous testing show that together the variables of capital intensity, managerial ownership, leverage, and financial distress have an effect on accounting conservatism.